(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The article discusses the current problems of investment management in conditions of high uncertainty, typical for the modern Russian economy. Special attention is paid to hedging strategies as an effective tool for reducing investment risks. The various types of risks faced by investors are analyzed and appropriate hedging strategies are considered, supported by real data and examples for the period 2021-2024. Recommendations are offered on choosing optimal hedging strategies depending on the specific conditions and goals of the investor.